Associations of Whole Grain and Refined Grain Consumption With Metabolic Syndrome. A Meta-Analysis of Observational Studies - Guo, Hongbin; Ding, Jun; Liang, Jieyu; Zhang, Yi (Frontiers in Nutrition, 2021)
Background: The associations of whole grain and refined grain consumption with metabolic syndrome (MetS) has been evaluated in several epidemiological studies with conflicting results. This meta-analysis was therefore employed to further investigate the above associations. Method: We searched the PubMed, Web of Science and Embase database until March 2021 (without restriction for inclusion time), for observational studies on the associations of whole grain and refined grain consumption with MetS. The pooled relative risk (RR) of MetS for the highest versus lowest category of whole grain and refined grain consumption, as well as their corresponding 95% confidence interval (CI) were calculated. Results: A total of 14 observational studies, which involved 7 cross-sectional and 7 prospective cohort studies, were identified. Specifically, 9 studies were related to whole grain consumption, and the overall multi-variable adjusted RR demonstrated that the whole grain consumption was inversely associated with MetS (RR=0.80, 95%CI: 0.67 to 0.97; P=0.021). With regard to refined grain consumption, 13 studies were included. The overall multi-variable adjusted RR indicated that refined grain consumption was positively associated with MetS (RR=1.37, 95%CI: 1.02 to 1.84; P=0.036). Conclusions: The existing evidence suggests that whole grain consumption is negatively associated with MetS, whereas refined grain consumption is positively associated with MetS. Our result might be helpful to better consider the diet effect on MetS. However, more well-designed prospective cohort studies are needed to elaborate the concerned issues further.